A Model Design for the Management of Moral (Akhlaq Karimah) Education in Modern Pesantren in Indonesia - Wanayati, Sri; Badrudin, Badrudin; Zaqiah, Qiqi Yuliati; Nursobah, Asep (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research aims to describe and analyze the model of moral (akhlaq karimah) education management at modern Islamic boarding schools (pondok pesantren). The research was conducted at Pondok Modern Tazakka Batang, Pondok Pesantren Darulrahman Jakarta, and Pondok Modern Darussalam Gontor. The research method used is qualitative with a multisite case study approach. The results show that the management of akhlaq karimah education in modern boarding schools employs a model based on exemplary behavior, the habitual practice of worship, and the active involvement of all components of the pesantren. A Structured and Sustainable Management System Strategic Planning in Moral Education in Modern Islamic Boarding Schools for Character Building Modern Islamic boarding schools have an important role in shaping the character of students to be in accordance with Islamic moral values. Effective strategic planning is needed to ensure that moral education can be implemented thoroughly and consistently in accordance with the Vision and Mission of Education, which is to form students who have noble character, high discipline, and are able to practice Islamic values in daily life. Students are accustomed to practicing Islamic manners such as time discipline, respecting teachers, and maintaining cleanliness. Moral education must be relevant to the challenges of the times, including the use of technology and social media.